Disaster insurance reimagined protection in a time of increasing risk - Jarzabkowski, Paula; Chalkias, Konstantinos; Cacciatori, Eugenia; Bednarek, Rebecca 19XX- (Oxford University Press, 2023)
This book is about the critical yet little-known work of "Protection Gap Entities" (PGEs), in disaster protection. Disasters, such as floods, earthquakes, and terrorist attacks, are becoming more frequent and more intense. These disasters threaten not only life, but also livelihood, causing the loss of homes and jobs that can scar the lives of those affected. Disaster insurance, by providing funds for reconstruction, plays an essential role in limiting these consequences of disaster. Yet disaster insurance is under threat in many contexts, becoming unaffordable or being withdrawn entirely. In response, many countries have established PGEs, organizations and schemes to keep disaster insurance available. PGEs rebalance the tensions (paradoxes) at the heart of insurance about who controls the insurance market, how much is known about the risk, and who should pay for protection. Using evocative examples from our research into 17 PGEs across 49 countries over five years, we explain how PGEs establish, maintain, and expand disaster insurance, and their role in the wider landscape of disaster resilience. We conclude by reimagining disaster insurance as a key tool in an ecosystem that has societal protection from disaster at its heart. Our book is accessible for those who have never heard of PGEs or thought about disaster insurance. We explain why PGEs are vital in adapting to an increasingly disaster-prone world. Our paradox lens on the tensions PGEs face will also provide an alternative, thought-provoking view for risk professionals working with the challenges of insuring disasters.